Pandemic of inequality gendered impacts of the COVID-19 recession in the Philippines labor market - Calma, Maria Alyssa Janella V.; Dancel, Marivic T.
The health and economic crisis associated with the emergence of the COVID-19 pandemic have impacted the Philippines harder than other developing countries, producing sizable economic contraction that challenged labor market conditions and exacerbated the state of inequality between the employment of men and women. Using data from the Labor Force Surveys, this study examines the gendered impacts of the COVID-19 recession in the Philippine Labor Market by doing a descriptive and estimation analysis of the primary labor market indicators namely employment, unemployment, and non-participation. Evidence shows that the impact of the pandemic goes far beyond health consequences. With the intensified needs for unpaid domestic and care work brought by school closures and stay-at-home orders, and particular impact on service sectors, women were disproportionately affected by the crisis as seen in their unemployment and non-participation rates throughout the quarters of 2020. Further, this study exposed that women have long been disadvantaged in the labor market with their consistently higher non-participation rate prior to the pandemic, and that this gender gap has even worsened during the COVID-19 recession. This study attempts to explain such disproportionate effects by exploring the role of industry distribution and demographic characteristics in the employment outcomes of men and women. These findings aim to inform policy responses in ensuring a more gender-inclusive recovery by highlighting the need for targeted actions that address the unequal impacts of the COVID-19 pandemic to the lives and employment conditions of men and women.